Modeling lateral facies heterogeneity of an upper Oligocene carbonate ramp (Salento, southern Italy). (September 2018) - Tomassetti, Laura; Petracchini, Lorenzo; Brandano, Marco; Trippetta, Fabio; Tomassi, Andrea
Abstract: The aim of this work is to reproduce a metre-scale facies heterogeneity 3D model of the Chattian Porto Badisco Calcarenite carbonate ramp outcropping in the Salento Peninsula (southern Italy). However, in shallow-water carbonate systems, capturing metre-scale facies heterogeneity in three-dimensional models remains controversial due to the possibility of facies coexistence and because their association can change through time and space. Within this context, the continuous and well-exposed Chattian Porto Badisco Calcarenite carbonate ramp allows detailed study of the distribution of lithofacies association and their architecture along the dip direction depositional profile. The lithofacies and the depositional model of the Porto Badisco Calcarenite are referred to those defined by Pomar et al. (2014). The Porto Badisco Calcarenite is a homoclinal carbonate ramp with a euphotic inner setting characterised by the extensive seagrass meadows, passing basinward into a large rotaliid packstone and coral mounds developed in mesophotic conditions. The deeper part of the oligophotic zone is characterised by rhodolithic floatstone to rudstone and large lepidocyclinid packstone. The distal part of the ramp is characterise by a fine calcarenite. The methodology used in this work combines classical field data collection (e.g., stratigraphic logs and field-facies mapping) and 3D stochastic modeling by using Petrel™. All the data (top and base of stratigraphic logs, cross-section, key surfaces, lithofacies lateral extension etc.) were georeferenced and inserted into the software to build the digital outcrop model. The 3D facies model has been performed after several simulations through specific stochastic algorithms (SISim, TGSim), comparing the models reproduce by the two algorithms, matching the depositional geometries and the lithofacies association observed in the outcrop. The 3D modeling represents a useful tool to better understand the facies architecture and their complex heterogeneity. Moreover, a detailed 3D facies model provides an essential tool to characterise semi-quantitatively sedimentological features for subsurface reservoir studies. Highlights: 3D modeling of facies heterogeneity in shallow-water carbonates is a useful tool to understand facies architecture and their complexity. Different simulation algorithms can produce different 3D-facies heterogeneity models. Algorithm choice has a strong impact on the reliability of spatial facies relationships and their distribution along a depositional profile.